Penelitian Budaya Suku Timor - Nasywa Aliyah K.; Putri Ichtiari D.W; Riyandhita Putri O; Viola Shafina; Zinnatun Nisa; Bambang Sri Wibowo (PUTRA JAWA PUBLISHER, 2023)
This research aims to explore the diverse aspects of Indonesian culture that have received limited attention from the community. Rather than allowing cultural differences to divide us as Indonesians, we should foster a sense of unity and brotherhood. The focus of this cultural research is the Rote tribe, residing in the Rote Ndao archipelago of the East Nusa Tenggara province, around 2020. The Rote tribe is one of several Timorese tribes that have settled on various small islands in East Nusa Tenggara. This tribe possesses unique attributes in terms of accessories, traditional clothing, and weapons. Male members of the Rote tribe typically wear plain white shirts with woven cloth instead of pants, and sometimes they only use a crossed cloth to cover the chest (exposing half of the chest). Female members wear closed woven cloth resembling overalls. Additionally, the Rote tribe has distinctive accessories, including a hat resembling a traditional Mexican hat, and a neck necklace called habas. Their special weapon is an axe, primarily used for cutting wood. Despite being somewhat blunt, this weapon is remarkably sharp, similar to a kris. Most residents of the Rote tribe speak the Austronesian language or Polynesian Malay, and many work as fishermen. This cultural heritage holds great value for the Indonesian people, as it reflects the identity of the Indonesian state. It is crucial for us, as Indonesians, to preserve the authenticity of this culture and its heritage.